Control of tool wear during turning of parts of construction and road machines in conditions of repair production - Ovsyannikov V.E.; Vasiliev V.I. (Научно-технический вестник Брянского государственного университета)
During repair actions, turning (weeding) is a fairly common method of treatment. At the same time, repair production uses mainly obsolete equipment and the qualification of machine-tools is often lower than in the manufacture of new products. A significant problem which makes it difficult to provide the required surface quality parameters is the wear of the cutting tool. By improving processing efficiency, active monitoring is implemented. The purpose of the work is to develop technical solutions that make it possible to estimate the life of the cutting tool during processing. Experimental studies were carried out on a 1I611PF2-grade turn-cutting machine. As a diagnostic feature, an acoustic signal in the range of 6 to 12 kHz was used to evaluate the wear of the cutting tool, since preliminary studies found that the range was most sensitive to changes in processing modes. Studies were performed at different wear values of the cutting tool (estimated by the width of the wear chamfer).Neuro-fuzzy model of estimation of cutting tool operation resource is developed. Use of models of this class gives the chance of fine tuning under specific conditions (the machine, the tool, etc.) and it is correct to estimate a resource of operation of the tool. Model error by test sample does not exceed 10%.